Honors. (16th July 2013) - Anonymous,
Abstract : The Geological Society of America's (GSA) new class of medal and award recipients and fellows includes many AGU members. Medal and award recipients areStephen G. Pollock, University of Southern Maine: GSA Distinguished Service Award;John R. Wheaton, Montana Bureau of Mines and Geology: John C. Frye Award;Clifford A. Jacobs, National Science Foundation (NSF): Outstanding Contributions Award, Geoinformatics Division;Peter Bird, University of California, Los Angeles (emeritus): George P. Woollard Award, Geophysics Division;Chunmiao Zheng, University of Alabama: O. E. Meinzer Award, Hydrogeology Division;Gerhard Wörner, Georg August Universität Göttingen: Distinguished Geologic Career Award, Mineralogy, Geochemistry, Petrology, and Volcanology Division;Alan D. Howard, University of Virginia: G. K. Gilbert Award, Planetary Geology Division;Michael E. Perkins, University of Utah: Kirk Bryan Award for Research Excellence, Quaternary Geology and Geomorphology Division; andPeter J. Hudleston, University of Minnesota: Career Contribution Award, Structural Geology and Tectonics Division.